Physical and Sensory Properties of Vegetarian Burger Patty - RAJARETNAM, SUGANYAA; Malik, Dr. NurHafizah (Enhanced Knowledge in Sciences and Technology, 2023)
The burger patty is considered a processed meat product that is usually produced by using minced chicken, lamb, pork, turkey, and other palatable meats. Excess cholesterol, sodium, and flavoring agents in commercial burger patties led to an unhealthy diet pattern and an increased consumer craving for fast food. This, ideally, results in elevated cholesterol levels in the blood, obesity, high blood pressure, and even the possibility of cancer. This study was aimed at observing the unripe soursop’s incorporation into the burger patty as the meat alternative and its effect on the physical and sensory properties. Therefore, 6 formulations of the burger patty were formulated, which were: F1 (mushroom 58%), F2 (soursop 58%), F3 (mushroom 29% + soursop29%), F4 (mushroom 29% jackfruit 29%), F5 (jackfruit 29% + soursop29%), F6 (mushroom 19.3% + jackfruit19.3% + soursop19.3%). The unripe soursop and oyster mushroom cleaned and dried (1 hour at 108˚C). Then, burger patty was formulated by minced the raw material (oyster mushroom and unripe soursop) using food processor and mixed with plant-based ingredients by referring to the quantity needed in the Table 3.1. Then, the combined ingredients were molded, frozen overnight (-18˚C) and then pan fried 2-10 minutes 180-200˚C. The physical properties (moisture, pH, color, TPA and cooking loss were evaluated on the formulated raw and cooked vegetarian burger patty as well as the sensory evaluations in term of appearance, taste, texture, aroma, and overall acceptance. All the data interpreted statistically using one way ANOVA. The physical properties parameter (moisture, pH, color, cooking loss) has attained significant reduction (p<0.05) meanwhile on the sensory evaluation, the vegetarian burger for F2 attained the higher acceptability.